ETUDE DE PROTECTION DE LA VILLE DE BAGHAI CONTRE LES INONDATIONS (W. KHENCHELA) - Beddiar, Mahdi; Souaiaia, Mohamed Tayeb (My University, 2023)
The problems of the natural risks in general and the floods in particular are a subject of topicality which marks a memorable section in the world and specifically in Algeria, in particular in comparison with the last years great catastrophic risings. Indeed, the management of this risk becomes more and more one requires which of which to include all the actors and all the means available possible. This study has as a more precise objective to determine the rain works and installations to set up on the basin slopes of the river Bourghal, for the protection of the town of Baghai against the floods. Our study consisted of several essential: parts hydrological study which allowed the determination of the probable flood flow, and hydraulic study for the calculation of the dimensions of the works of installations. -------------------------------------------------------------------------- يعد مشكل الكوارث الطبيعية بشكل عام والفيضانات بشكل خاص موضوعًا هاما في العالم وخاصة في الجزائر، وفي ضوء الفيضانات الكارثية الأخيرة، أصبحت إدارة هذا الخطر ضرورة أكثر فأكثر والتي يجب أن تشمل جميع الجهات الفاعلة وجميع الوسائل المتاحة الممكنة. وتهدف هذه الدراسة تحديد هياكل الحماية التي سيتم تنفيذها على مستوى وادي بورغال، لحماية مدينة بغاي من الفيضانات. تألفت دراستنا من عدة أجزاء أساسية: دراسة هيدرولوجية سمحت بتحديد التدفق المحتمل للفيضان، ودراسة هيدروليكية لحساب أبعاد أعمال المنشآت ---------------------------------------------------------------------- La problématique des risques naturels en général et des inondations en particulier est un sujet d’actualité qui marque une section mémorable dans le monde et spécifiquement en Algérie, notamment au regard des dernières années grandes crues catastrophiques. En effet, la gestion de ce risque devient de plus en plus une nécessite qui doit inclure tous les acteurs et tous les moyens disponibles possibles. Cette étude a pour objectif plus précis de déterminer les ouvrages d’aménagements à mettre en place sur le bassin versant de l’oued bourghal, pour la protection de la ville de baghai contre les inondations. Notre étude s’est composée de plusieurs parties essentielles Une étude hydrologique qui a permis la détermination du débit de crue probable, et Une étude hydraulique pour le calcul des dimensions du les ouvrages d’aménagements.